Biological Activity of Saussurea Costus Extract on MDR Enterobacter Spp - Al-khateeb, Shareef Saleh Mahdi; Mahdi, Nisreen Ahmed; al-Thabhawee, Sarah Mohammed Hussein; ALMUSAWI, AMJED MOHAMMED SAHIB (Journal of Science in Medicine and Life, 2025)
Enterobacter spp. are common pathogens causing a variable spectrum of the infection are a main reason of nosocomial and opportunistic infection in hospitals also can be found in the gastrointestinal tract. The aim of this study is to diagnose Enterobacter spp. that cause bacteremia, infections for both the urinary as well as respiratory tracts, inflammations of joins and endocardium, infections of ophthalmic, intra-abdominal and bones among other extra intestinal infection multiple resistance to a group of antibiotics in patients admitted to the Al-Sadr Teaching Hospital in Al-Najaf. Where 102 samples were collected, among 102 clinical specimens from different sources were 50 (48.32%) positive bacterial growth as following 12 (23.7%) return to gram-positive and 38 (76.3%) as gram-negative compared with 52 (51.67%) with no growth. This study also showed 6 clinical isolates of Enterobacter return to different species however these species ware isolated from various infections such as UTI, vaginal infection, burn wound infection, knee fluid, throat infection and intestinal infection and this explains the ability of this pathogen to infection various parts of human which may be due to the important virulence factors which help it to opportunist any conditions for infection , Where he tested the drug sensitivity of isolates and used 13 types of antibiotics by the method of tablet spread.